Reservas de carbono orgánico en diferentes tipos de utilización de la tierra - George Martín-Gutiérrez; Pablo Pablos-Reyes; Yakelín Cobo-Vidal; Juan Alejandro Villazón-Gómez (Pastos y Forrajes)
Objective: To evaluate the effect of different types of land use on organic carbon stocks in a typical dark red ferritic soil. Materials and Methods: The research was developed in a permanent observation point, located in the Guaro locality, Mayarí municipality, Holguín province. Soil samples were taken at 0-20, 20-40 and 40-60 cm depth, in three types of land use: Pinus cubensis Griseb. forest, natural pasture (Paspalum notatum Alain ex Flügge) and Saccharum spp. to which total organic carbon was determined. In addition, undisturbed samples were taken to determine the bulk density. Results: Significant differences in soil organic carbon stocks were found among the three types of land use, at a depth of 0-20 cm. The natural pasture had the highest stock. It was followed by Saccharum spp and P. cubensis forest. There was increase in the rate of edaphic carbon accumulation with depth in all types of land use. The highest values were found in the 0-20 cm depth, which decreased with profile. There were negative figures only in the P. cubensis forest, at 40-60 cm depth. Conclusions: The highest carbon stocks were found in soils with P. notatum. This was followed by Saccharum spp. and P. cubensis. Land use types with less human activity showed the highest rates of carbon accumulation and better soil quality.